EVOLUTION OF ARCHITECTURAL STYLE - Naaz, Shaila; C., Lalrinkima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Architecture has always been important throughout history, showing what people value, how technology changes, and what society needs. The way buildings have changed over time is interesting. It’s like a story that shows how different cultures, societies, technology, and art have all mixed together. The aim of this research paper is to establish a comparative study of architecture evolution style over the period over the period. The paper will talk about the architectural styles of different time and do a comparative analysis to come for a conclusion. It is necessary to study and compare the evolution in architecture as it will help us in knowing what kind of evolution happen, when were new architecture introduced and so on. As we keep moving forward, buildings show how smart and creative people are, and they give us spaces that make us think and feel in different ways, making life more interesting for everyone.